2023
DOI: 10.3390/diagnostics13162668
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Volume Change—A Candidate for a New Radiological Marker of MS Progression

Abstract: (1) Background: Multiple sclerosis (MS) is an auto-immune, chronic, neuroinflammatory, demyelinating disease that affects mainly young patients. This progressive inflammatory process causes the chronic loss of brain tissue and results in a deterioration in quality of life. To monitor neuroinflammatory process activity and predict the further development of disease, it is necessary to find a suitable biomarker that could easily be used. In this research, we verify the usability of choroid plexus (CP) volume, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Fleischer and colleagues, on the other hand, demonstrated a significant correlation between CP enlargement and clinical disability (EDSS score) in a cohort of CIS and RRMS individuals, both cross-sectionally and longitudinally, after 4-year follow-ups, supporting the clinical relevance of plexus volumetric analysis, among others [5,23,30]. Cognitive impairment, measured with the Symbol Digit Modalities Test (SDMT) score, was also associated with plexus enlargement [23].…”
Section: Klistorner Et Al Failed To Show a Correlation Between Cpv An...mentioning
confidence: 90%
See 3 more Smart Citations
“…Fleischer and colleagues, on the other hand, demonstrated a significant correlation between CP enlargement and clinical disability (EDSS score) in a cohort of CIS and RRMS individuals, both cross-sectionally and longitudinally, after 4-year follow-ups, supporting the clinical relevance of plexus volumetric analysis, among others [5,23,30]. Cognitive impairment, measured with the Symbol Digit Modalities Test (SDMT) score, was also associated with plexus enlargement [23].…”
Section: Klistorner Et Al Failed To Show a Correlation Between Cpv An...mentioning
confidence: 90%
“…Similarly, Ricigliano and colleagues did not find an association between the enlarged and inflamed CP and the severity of clinical disability, as measured by the EDSS score, but the plexus volume was markedly associated with the annual relapse rate in the RRMS group [15]. Jankowska et al also confirmed that CP enlargement was connected to relapses in RRMS individuals, but it should be mentioned that it was a relatively small group (14 people) [30].…”
Section: Clinical Implications Of Plexus Enlargementmentioning
confidence: 94%
See 2 more Smart Citations
“…For example, in our recent study we observed that the choroid plexus volume correlates with the activity of the inflammatory process in the CNS in MS patients. We proposed that it could become a valuable radiological biomarker of MS activity [ 34 ].…”
Section: Future Directionsmentioning
confidence: 99%